Doses de fósforo no desenvolvimento inicial e produção de forragem de cultivares de Panicum maximum - Torres, Francisco Eduardo; Teodoro, Paulo Eduardo; Ribeiro, Larissa Pereira; de Oliveira, Elisa Pereira [UNESP]; de Oliveira, Marcus Vinicius Morais; da Silva Junior, Carlos Antonio; Corrêa, Caio Cezar Guedes (My University, 2016)
Phosphorus shortage in the Savanna is one of the main limiting factors for forage production and directly responsible for the degradation of pastures in this Brazilian region. Thus, the aim of this study was to evaluate the effect of increasing doses of P on the initial development and forage production of four cultivars of P. maximum. The experiment was conducted during the months of December 2010 to May 2011 at Universidade Estadual de Mato Grosso do Sul, Unit of Aquidauana-MS. It was used the completely randomized design in a factorial scheme 4x5, with four replications. The experimental unit consists of polyethylene pots with 5 L capacity arranged in countertop in greenhouse. The first factor consisted of four P. maximum cultivars (Massai, Mombaça, Áries and Atlas), while the second factor consists of five doses of phosphorus (0, 5, 10, 30 and 45 mg dm-3). It was evaluated the following morphometric traits: plant height, length and width of the leaf blade, number of tillers, dry mass of shoot and of roots at 60 DAS. The approximate dose of 25 mg dm-3 of phosphorus provided better initial development and forage production in all cultivars evaluated of Panicum maximum. Mombaça cultivar has better initial development and forage production about to the others.
Doses of phosphorus on initial development and forage production of cultivars of Panicum maximum
Keywords: Degraded pastures; Morphometric characters; Phosphate fertilizer